Analisis Fungsi Inspeksi Unit Apron Movement Control (AMC) dalam Menunjang Kedisiplinan Petugas Apron di Bandar Udara Supadio Pontianak - Malinda Maharani; Raden Fathul Hilal (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Apron Movement Control (AMC) Unit is a vital component in airport operations, playing an important role in ensuring the safety and efficiency of flight services. This study aims to determine what obstacles are encountered during inspection activities and how does the Apron Movement Control (AMC) unit overcome these obstacles. This study uses a qualitative approach with field observations and then conducting analysis. The subjects of this study were Apron Movement Control (AMC) Unit officers at Supadio Airport, Pontianak. The research period was 1 month. The results of the study can be concluded that the main obstacles of the AMC unit at Supadio Airport, Pontianak include communication difficulties due to noise, limited visual supervision, and coordination between units. The proposed solutions include improving communication systems, expanding surveillance camera coverage, optimizing personnel, regular training, using new technologies such as drones, and evaluating and improving operational procedures. The implementation of these solutions is expected to improve the effectiveness of the AMC inspection function, support the discipline of apron officers, and improve the safety and smoothness of airport operations..